A comparison between the morphological and molecular approach to identify the benthic diatom community in the St Lucia Estuary, South Africa. Issue 4 (17th December 2019) - Nunes, M; Adams, JB; Van Aswegen, S; Matcher, GF
Abstract : The use of diatoms as bioindicators to detect human-induced change is a globally accepted monitoring tool. DNA metabarcoding is an effective complementary tool to standard microscopic methods for species identification, providing reliable and timeous diatom assessments in a range of aquatic ecosystems. This study evaluated the suitability of the DNA metabarcoding approach for diatom monitoring in the St Lucia Estuary, South Africa. Results obtained from the standard microscopic (morphological) and molecular methods were compared and indicated a low similarity in the vegetated (11%), unvegetated (12%) and epiphytic (12%) habitats at species level for the epipelic and epiphytic diatom communities. The difference between the methods was expected given the challenges pertaining to the incomplete molecular reference database, intragenomic variability, physiological differences (number of chloroplasts) and highly variable microphytobenthos biomass. While the molecular method was unable to identify the presence of all the dominant diatom species (routinely used as ecological indicators), the available molecular operational taxonomic units (MOTUs) provided an effective complementary tool to determine the relevant community diversity estimates required for the application of the South African estuarine health index (EHI).